Dislexia e escola: um olhar crítico sobre a equipe multidisciplinar e sua relação com as práticas pedagógicas tendo como foco o professor. - Vasconcelos, Diva Helena Frazão de (2011)
This work aimed to identify what 5th grade teachers from private and public schools of João Pessoa, PB, knew about dyslexia, besides the pedagogic practices developed with the teachers to help dyslexics and the interaction between schools staff and the professionals specialized in treating this learning disorder. We focused the 5th grade teachers because it is supposed that students have already got over the expected difficulties of reading and writing acquisition at this time. Dyslexia is a social serious and numerous problem, according to Brazilian Dyslexia Association (ABD), but has not received a proper attention from health and education public offices and has even been excluded from the assistance program ruled by the Secretaria de Educação Especial of Brazilian Ministério de Educação e Cultura. The research was based on Vygotsky s social-interactive theory and on some other researchers of equal importance and scientific orientation, such as Kleiman (2007), Perrenoud (2001), Ong (1998) and Marcuschi (2004). The data were collected from bibliographic sources, interviews and questionnaires applied to twenty 5th grade teachers, ten public and private school technicians and eight professionals of the multidisciplinary team of dyslexia diagnosis and treatment. Surveys about the importance of teachers help to dyslexics hardly exists, in spite of the emphasis and information coming from cognition studies that point to the relevance of teacher s mediation to students get over reading and writing difficulties. This research pointed to little knowledge about this learning disorder among teachers, due mostly to inadequate academic and continuous formation course curriculum. It also showed that there is intense communication between health professionals and private schools what does not happen between them and public schools.